Dung beetles (Coleoptera: Scarabaeinae) of El Goaltal, Carchi, Ecuador: annotated list of species and ecology - Santiago Villamarín-Cortez (ACI Avances en Ciencias e Ingenierías, 2010)
Between the months of August 2003 and February 2004, conducted a study about the dung beetles of El Goaltal, Carchi Province, Ecuador. Fourteen transects were established for the study (seven in highland grasslands or páramos and seven in altered forest) where pitfall traps were used, baited with human feces and carrion. In total, 2982 individuals belonging to 22 species were obtained. The general abundance was larger in secondary forests, with 4.4 times more captured beetles than in grasslands.